Systematic Literature Review Pengembangan Kurikulum Adaptif Sekolah Dasar Di Era Digital - Triyani; Keriyah; Liyana Sunanto (PT. AHLAL PUBLISHER NUSANTARA, 2025)
The rapid development of digital technology requires education systems, particularly at the elementary level, to adapt their curricula to meet the demands of the 21st century. This study aims to identify trends, approaches, models, challenges, and opportunities in the development of adaptive curricula through a Systematic Literature Review (SLR). The review analyzed scholarly articles published between 2013 and 2025, focusing on elementary schools in Indonesia. Findings indicate that adaptive curriculum development is commonly carried out through the integration of information and communication technology (ICT), material modification, media, and evaluation methods, as well as the application of inclusive principles. Major obstacles include limited digital infrastructure, low teacher digital literacy, and regional disparities between urban and rural schools. Nevertheless, adaptive curricula have proven effective in enhancing student engagement and comprehension. This study offers policy recommendations for inclusive, technology-based educational reforms and highlights the need to strengthen teacher capacity in addressing digital challenges in elementary education. Keywords: adaptive curriculum, elementary school, digital era, inclusive education, educational technology. Abstrak Perkembangan teknologi digital yang pesat menuntut sistem pendidikan, khususnya di tingkat sekolah dasar, untuk menyesuaikan kurikulum agar lebih adaptif terhadap kebutuhan abad ke-21. Penelitian ini bertujuan untuk mengidentifikasi tren, pendekatan, model, tantangan, dan peluang dalam pengembangan kurikulum adaptif berbasis digital melalui metode Systematic Literature Review (SLR). Kajian dilakukan terhadap berbagai artikel ilmiah yang diterbitkan antara tahun 2013 hingga 2025, dengan fokus pada sekolah dasar di Indonesia. Hasil telaah menunjukkan bahwa pengembangan kurikulum adaptif banyak dilakukan melalui integrasi teknologi informasi dan komunikasi (TIK), modifikasi materi, media, dan metode evaluasi, serta penerapan prinsip inklusivitas. Kendala yang umum ditemui mencakup keterbatasan infrastruktur digital, rendahnya kompetensi digital guru, serta disparitas wilayah antara sekolah di perkotaan dan pedesaan. Meski demikian, kurikulum adaptif terbukti meningkatkan partisipasi dan pemahaman siswa terhadap materi ajar. Hasil studi ini memberikan rekomendasi kebijakan pendidikan berbasis teknologi yang inklusif dan kontekstual, serta mendorong penguatan kapasitas guru dalam menghadapi tantangan digitalisasi pendidikan dasar. Kata Kunci: Kurikulum Adaptif, Sekolah Dasar, Era Digital, Pendidikan Inklusif, Teknologi Pendidikan.